Study of Transportation Movement Generation in Bandung City by using QuickBird Imagery Remote Sensing and Geographic Information System - Somantri, Lili (Universitas Muhammadiyah Surakarta, 2013)
The objective of this study is to examine the transport movement generation in Bandung City by using QuickBird imagery remote sensing and Geographic Information Systems. The method used in this research is spatial approach by quantitative descriptive analysis. It resulted that the greatest movement generation come from the regular housing types of 3440 people per hour. The District with the greatest generation was Sub Ujungberung, i.e. 55,501 people per hour, whereas the highway with the greatest amount of generation is Soekarno-Hatta Street of 51,014 people per hour.